Beneficial and Safety Properties of a Bacteriocinogenic and Putative Probiotic Latilactobacillus sakei subsp. sakei 2a Strain - Tatiana Alexandrovna Lipilkina; Cristhian Xu; Matheus de Souza Barbosa; Valentina Nikolaevna Khramova; Sergei K. Shebeko; Alexey M. Ermakov; Iskra Vitanova Ivanova; Svetoslav Dimitrov Todorov (Foods)
This work aimed to evaluate some of the probiotic features and safety of the bacteriocin-producing Latilactobacillus sakei subsp. sakei 2a. The effect of selected commercial drugs from different generic groups and antibiotics on the growth of Ltb. sakei subsp. sakei 2a was also determined. The presence of virulence factors was determined based on PCR with total DNA from Ltb. sakei subsp. sakei 2a. Good growth of Ltb. sakei subsp. sakei 2a was recorded in MRS broth supplemented with 0.2% or 0.4% oxbile or in MRS broth adjusted to a pH from 5.0–9.0. Auto-aggregation of Ltb. sakei subsp. sakei 2a was 62.59%. Different levels of co-aggregation were recorded between Ltb. sakei subsp. sakei 2a and Enterococcus faecalis ATCC19443, Ltb. sakei ATCC15521 and Listeria monocytogenes ScottA. Growth of Ltb. sakei subsp. sakei 2a was not inhibited by commercial drugs from different generic groups. The inhibitory effect on the growth of Ltb. sakei subsp. sakei 2a was recorded only in the presence of Arotin [selective serotonin reuptake inhibitor antidepressant] Minimal Inhibition Concentration (MIC) 1.0 mg/mL, Atlansil [Antiarrhythmic] MIC 0.625 mg/mL, Diclofenac potassium [non-steroidal anti-inflammatory drug (NSAID)] MIC 2.5 mg/mL and Spidufen [NSAID] MIC 15.0 mg/mL. Only two antibiotics tested in this study, Amoxil and Urotrobel, inhibited the growth of Ltb. sakei subsp. sakei 2a with a MIC of <0.5 mg/mL and 5.0 mg/mL, respectively. However, Ltb. sakei subsp. sakei 2a generated positive PCR results on the DNA level for vanA (vancomycin resistance), hyl (hyaluronidase), esp (enterococcal surface protein), ace (adhesion of collagen) and cilA (cytolisin) and a high virulence profile when examined for the presence of virulence factors. It is important to underline that cytolysis has been described as a virulence and antibacterial factor.